When Polanyi met Farage: Market fundamentalism, economic nationalism, and Britain's exit from the European Union - Hopkin, Jonathan (British Journal of Politics & International Relations, 2017)
The vote for Brexit is not an isolated event, but part of a wave of populist, anti-elite revolts: a new 'anti-system' politics Western democracies are experiencing, shaking the existing consensus around economic integration, free markets and liberal values. This wave takes a variety of forms, but has in common a robust, even violent, rejection of the mainstream political elites and their values, and a demand for governments to act on the sources of social and economic distress and inequality. This article views Brexit as a part of this new anti-system politics, a reaction to the decline in ideological competition in democracies and the increasing impotence of politicians to address the upheavals wrought by global free market capitalism. This reaction has become particularly acute after the financial crisis of the late 2000s, which affected Britain disproportionately, and the failure of austerity policies to revive growth, crystallising the ineffectiveness of existing policies to deal with economic stagnation and cultural change. This policy failure is compounded by a perceived refusal of politicians to engage with the broader public and a lack of real choice between the mainstream political parties. The article will present evidence that a failed policy consensus, a rise in inequality and a decline in the representativeness of political elites, rather than a resurgence of intolerance or xenophobia, are the principal causes of the Brexit vote.
Political Science
Keywords: Brexit; British economic policy - 2010-; British withdrawal from the European Union; 2016-; Europe - Foreign relations - Great Britain; European Union; Great Britain - politics & government - 2007-; economic nationalism; economics; markets; membership; nationalism; protectionism